Predisposing Characteristic of MSM (Men who Have Sex with Men) in Utilizing of CST (Care Support and Treatment) Services in Jember District - Khamid, M Nur; Marchianti, Ancah Caesarina Novi; Rokhmah, Dewi (Health Notions, 2018)
MSM behavior in Indonesia still become an important issue in our society and some of our society canât accepted the MSM. The prevalence of HIV in MSM population is such a warning and need to be concerned. Data from Jember District Health Office showed that from 2004 until June 2017, the number of HIV AIDS were 3186 cases, based on homosexual risk factor were 7.6%. This research aimed to analyze predisposing characteristic of MSM with HIV positive such as: 1) Demoghraphy: sex, age, marriage status, place of live, the region, and education background, 2) The distance from home to the CST services, 3) Health belief. This study used qualitative method with case study approach. There were 8 main informants and recruited purposively. Data was collected by in depth interview and analyzed with thematic content analysis. The result showed that most of informants aged 25-30 years old, a small number of informants in 20-23 years old. The distance of home and CST services influenced the MSM with HIV positive to drink drug regularly.The effort of informants to care their health were obedient in ARV treatment, taking care to dietary habits, doing exercise regularly and avoid their self from stress. The side effect of ARV are dizzy, nausea, vomiting, fatigue or pain in some of hinge, appetite loss and mood changes. The effort to make an obedient in ARV treatment need to add the CST sevices in Center of public health and make ARV satelite Center of public health in every district, role model, optimilize the guidance to the MSM with HIV positive, to prevent the loss to follow up because the side effect and to give a support in obeidient the ARV treatment. Keywords: MSM, HIV, Care Support and Treatment